Accelerated charging of PCM in a horizontal shell and multi-finned tube energy storage system. (2021) - Anish, R.; Mariappan, V.; Hitha, P.S.; Arun, B.S.
Abstract: An experimental study is carried out to analyze the melting behaviour of erythritol in an energy storage unit with multi-finned tubes. Temperature variation of erythritol in different locations of the storage unit and rate of heat storage during the charging process were obtained. Melting of PCM was a faster process owing to the effect of additional natural convection. During melting, molten PCM primarily occupies in the upper region of energy storage unit (ESU) and then extends towards the bottom region. The lower part of the storage unit is mostly dominated by conduction while the upper part of the ESU is controlled by natural convection. Compared to the heat transfer fluid (HTF) inlet temperature, volume flow rate shows slight influence on the melting process. Furthermore, storage unit with longitudinal multiple tubes gave the best thermal performance and significant increase in the rate of PCM melting were achieved during the ESU charging process. The result of this analysis is expected to be helpful for concentrated solar power systems and other thermal systems design.